2020
DOI: 10.1002/agj2.20309
|View full text |Cite
|
Sign up to set email alerts
|

Breaking rice yield barrier with the ratooning method under changing climatic conditions: A paradigm shift in rice‐cropping systems in southwestern Japan

Abstract: Rice (Oryza sativa L.) ratooning has recently attracted attention since it possesses higher yield potential compared to conventional rice-growing methods; however, it requires a longer growing season. Field experiments were conducted in southwestern Japan in 2017 and 2018 to determine the effect of harvest time (early and normal) and cutting height (high and low) of the first crop on grain yield of the first and second crops using a high-yielding line under high N application and high air temperature condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 30 publications
3
38
1
Order By: Relevance
“…We recently reported that a high total grain yield of the first and second crops (14.4 t ha -1 ) was produced in rice ratooning when the first crop was harvested at the normal time (1,200 °C days, cumulative mean air temperature from heading to harvest) with a high cutting height (50 cm from the ground surface) under high N application rate and air temperature conditions (Nakano et al, 2020b). The rice growing season will be extended in the near future since the world's average temperature is predicted to increase by 0.3-4.8 °C depending on the emissions scenario (IPCC, 2014).…”
Section: Future Prospectmentioning
confidence: 99%
“…We recently reported that a high total grain yield of the first and second crops (14.4 t ha -1 ) was produced in rice ratooning when the first crop was harvested at the normal time (1,200 °C days, cumulative mean air temperature from heading to harvest) with a high cutting height (50 cm from the ground surface) under high N application rate and air temperature conditions (Nakano et al, 2020b). The rice growing season will be extended in the near future since the world's average temperature is predicted to increase by 0.3-4.8 °C depending on the emissions scenario (IPCC, 2014).…”
Section: Future Prospectmentioning
confidence: 99%
“…Rice is a staple food eaten by nearly half the world's populations (GriSP, 2013); thus, it provides food security for many developing nations. Rice ratooning could contribute to resolving the global food crisis by improving the total grain yield of the first and second crops (Nakano, Tanaka, Wada et al., 2020). Moreover, a recent study reported that the net economic return of ratooned rice was higher than those of single‐cropped mid‐season rice and double‐season rice (Yuan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Grain yields of the first and second crops are affected by the harvest time of the first crop. Recently, in southwestern Japan, we examined the effect of harvest time (before maturity and at maturity) and cutting height (20 and 50 cm from the ground surface) of the first crop on the grain yields of the first and second crops under high N application conditions using a high‐yielding line derived from a cross between Hokuriku 193 and an F1 cross between Hokuriku 193 and Bekoaoba (Nakano, Tanaka, Wada et al., 2020). Our results revealed that plants harvested at a cutting height of 50 cm produced a higher grain yield than those harvested at 20 cm.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, rice plantations account for approximately 35% (1.6 million ha) of total arable land. Field experiments aiming to enhance rice yields have been conducted in southwestern Japan (Nakano & Tsuchiya, 2012;Nakano, Morita, Kitagawa, Wada, & Takahashi, 2012, Nakano et al, 2020. Nitrogen (N) is the most important nutrient in rice fertilizer (Yoshida, 1981) and known to increase chlorophyll synthesis, photosynthetic rate, and leaf area index (Akita, Parago, & Coronel, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, rice plantations account for approximately 35% (1.6 million ha) of total arable land. Field experiments aiming to enhance rice yields have been conducted in southwestern Japan (Nakano & Tsuchiya, 2012; Nakano, Morita, Kitagawa, Wada, & Takahashi, 2012, Nakano et al., 2020).…”
Section: Introductionmentioning
confidence: 99%